Direct Marketing Strategy To Increase Sales of SME Production in Budo Village, Wori District – North Minahasa Regency, North Sulawesi Province - Supit, Vekky; Langi, Cysca (Asian Journal of Logistics Management, 2022)
Budo Village in Wori District, North Minahasa Regency is a one of the assisted villages of the Manado State Polytechnic which is rich in resources nature is like marine tourism. The prima donna are coconut plants and their shells made souvenirs. However, sales activities are still not productive because marketing activities only rely on the traditional way of selling directly to consumers. Therefore, the role of marketing is very important. Marketing is an economic action that is very influential on the high and low income of producers. Good production will be in vain if the price the market is low, because high production does not automatically provide high profits without being accompanied by good and efficient marketing. Pre-research results show that internally, having a workforce sufficient, adequate raw material but facilities, business capital and technology insufficient. This study aims to identify the description of Direct Marketing of coconut shell souvenirs, analyzing the promotional activities carried out, formulate Direct Marketing that already uses social media. This study method uses a qualitative descriptive method. Data collection in this research study uses primary data sources of observations and interviews as well as data sources secondary through documentation. The results to be obtained are the application of direct marketing in SMEs is good, and already using a promotional mix strategy one of which is direct marketing by using media.internet. Outcomes to be achieved Final report, Scientific publications in journals Nationally accredited, Final Project for management study program students marketing involves two sixth semester students and teaching materials. First stage of proposal making, second stage of site survey and collection data, the third stage of data processing, training groups to promote and selling using social media, presentation and improvement, the fourth stage of report submission and the fifth stage of publication.